Standardization Of Traditional Sambareh Food Recipes - Efendi, Elma Wahyuni; Gusnita, Wiwik; Siregar, Juliana; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Thebackground to this research is that there is no standard sambareh recipe in Nagari Pakandangan, Enam Lingkung District, Padang Pariaman Regency, because there are still differences in ingredients and the measurements used and the processing process. this research aims to standardize the sambareh recipe in Nagari Pakandangan, Enam Lingkung District. This type of research uses a mixed method between quantitative and qualitative descriptive. Qualitative data collection techniques are observation, interviews, documentation and quantitative data collection techniques are organoleptic questionnaire format. Technique Active qualitative data analysis uses three activity stream, namely data reduction, data presentation, drawing conclusions and quantitative data analysis techniques using the formula (Mx=∑ x / N), data validity, testing the validity of qualitative data, namely: extended participation, diligent observation, and triangulation. Based on the research results, 3 sambareh recipes were obtained. The results of the organoleptic test obtained the highest score by Mrs. Erdayanti from Korong Kampuang Paneh with an average score of 23,4.  standardization of the sambareh recipe is carried out by organoleptic tests to obtain good quality Sambareh including: Sambareh shape (neat), color of Sambareh (white), aroma of Sambareh (fragrant combination of the addition of other ingredients), texture. sambareh (soft and nesting) and the taste of sambareh (savory).